Golden Silk Spider, Trichonephila clavipes (Linnaeus) (Arachnida: Araneae: Tetragnathidae) - H.V. Weems; G.B. Edwards (EDIS)
This document provides an in-depth profile of the golden silk spider, Trichonephila clavipes, native to Florida and other southeastern states. It describes the spider's physical characteristics, habitat, and behavior, including its web-building and prey-capture techniques. The article also covers the spider's life cycle, distribution, and interactions with other species. Despite its intimidating appearance, the golden silk spider poses little danger to humans, with bites causing only minor localized pain. The document is part of the Featured Creatures collection, aimed at both laypersons and academic audiences interested in entomology. Published: August 2001.